Suppression of TDO‐mediated tryptophan catabolism in glioblastoma cells by a steroid‐responsive FKBP52‐dependent pathway. Issue 1 (5th August 2014) - Ott, Martina; Litzenburger, Ulrike M.; Rauschenbach, Katharina J.; Bunse, Lukas; Ochs, Katharina; Sahm, Felix; Pusch, Stefan; Opitz, Christiane A.; Blaes, Jonas; von Deimling, Andreas; Wick, Wolfgang; Platten, Michael
<x xml:space="preserve">Abstract</x> Tryptophan catabolism is increasingly recognized as a key and druggable molecular mechanism active in cancer, immune, and glioneural cells and involved in the modulation of antitumor immunity, autoimmunity and glioneural function. In addition to the pivotal rate limiting enzyme indoleamine‐2, 3‐dioxygenase, expression of tryptophan‐2, 3‐dioxygenase (TDO) has recently been described as an alternative pathway responsible for constitutive tryptophan degradation in malignant gliomas and other types of cancer. In addition, TDO has been implicated as a key regulator of neurotoxicity involved in neurodegenerative diseases and ageing. The pathways regulating TDO expression, however, are largely unknown. Here, a siRNA‐based transcription factor profiling in human glioblastoma cells revealed that the expression of human TDO is suppressed by endogenous glucocorticoid signaling. Similarly, treatment of glioblastoma cells with the synthetic glucocorticoid dexamethasone led to a reduction of TDO expression and activity in vitro and in vivo. TDO inhibition was dependent on the immunophilin FKBP52, whose FK1 domain physically interacted with the glucocorticoid receptor as demonstrated by bimolecular fluorescence complementation and in situ proximity ligation assays. Accordingly, gene expression profile analyses revealed negative correlation of FKBP52 and TDO in glial and neural tumors and in normal brain. Knockdown of FKBP52 and treatment with the FK‐binding immunosuppressant FK506 enhanced TDO expression and activity in glioblastoma cells. In summary, we identify a novel steroid‐responsive FKBP52‐dependent pathway suppressing the expression and activity of TDO, a central and rate‐limiting enzyme in tryptophan metabolism, in human gliomas. GLIA 2015;63:78–90